Combination of GC-MS and selective peak elimination procedures as a tool for characterization of complex saccharide mixtures - Application to pyrolysis bio-oils - Kejla, Lukáš; Auersvald, Miloš; Šimáček, Pavel (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2021)
In this study, a GC-MS method was developed for the quantification of saccharides in complex mixtures such as bio-oils and bio-oil aqueous phases produced by ablative pyrolysis of lignocellulosic biomass. The samples were first treated using N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA) and the trimethylsilylated (more volatile) derivatives were analyzed by GC-MS. The method offers advantages of great separation capability and simultaneous identification of unknown peaks by comparison of the mass spectra and retention indices with extensive libraries available online. However, even with these tools at hand, the identification of several saccharide-resembling compounds can be challenging especially in such highly complex samples as pyrolysis bio-oils. For this reason, we devised a novel procedure, which eliminates certain saccharides depending on their specific chemical properties before subjecting the samples to the GC-MS analysis. The procedure was based on the combination of aniline treatment (elimination of reducing aldoses), and hydrolysis (elimination of anhydrosugars, glycosides, disaccharides and oligosaccharides). Based on the differences in chromatograms before and after the procedure, the unknown compounds were assigned into groups based on their susceptibility to each treatment. The combination of all methods above has allowed more accurate identification and quantification of saccharides, some of which were not as of today found in bio-oils.
Keywords: hydrolýza; vysoká teplota; Linear Models; Bio-oils; Saccharides; Aniline Compounds; Biofuels; Hot Temperature; Reproducibility of Results; cukry; GC–MS; Aniline treatment; Silylation; lineární modely; aniliny; reprodukovatelnost výsledků; limita detekce; plynová chromatografie s hmotnostně spektrometrickou detekcí; Hydrolysis; Gas Chromatography-Mass Spectrometry; Limit of Detection; Sugars; biopaliva